Efficacy and long-term outcomes of drug coated balloon in de novo lesions of small versus large coronary vessels - Hesham Refaat; Mohamed Arab (Indian Heart Journal)
Objective: Drug eluting stent (DES) could result in both in-stent restenosis and high bleeding risk due to long-term anti-platelet therapy. Drug-coated balloon (DCB) delivers anti-proliferative drugs without implanting metal into vascular wall. Our aim was to investigate its feasibility in large vessel coronary artery disease (LvCAD), compared to small vessel coronary artery disease (SvCAD). Methods: This study enrolled 237 patients with de novo coronary lesions treated with DCB-only strategy and categorized according to the reference vessel diameter of 3 mm into SvCAD and LvCAD groups. The primary endpoint was in-lesion late lumen loss (LLL). The secondary endpoints included composite major adverse cardiac events (MACE), cardiac death, non-fatal myocardial infarction (MI), target lesion revascularization (TLR), target vessel revascularization (TVR), and vessel thrombosis. Results: The immediate (3.06 ± 0.25 vs. 2.33 ± 0.21 mm, p = 0.001) and follow up minimal lumen diameter (3.13 ± 0.25 vs. 2.41 ± 0.21 mm, p = 0.001) and acute gain (1.92 ± 0.29 vs. 1.5 ± 0.26 mm, p = 0.04) were significantly higher in LvCAD group. In-lesion LLL was negative without significant difference (-0.07 ± 0.02 vs. - 0.06 ± 0.04 mm, p = 0.69). The incidence of adverse clinical events was not statistically significant accounting for 6.5 % vs. 10.5 % for composite MACE (p = 0.27), 0.8 % vs. 0.9 % for cardiac death (p = 0.96), 4.9 % vs.7 % for non-fatal MI (p = 0.49), 4.1 % vs. 6.1 % for TLR (p = 0.47), 2.4 % vs. 3.5 % for TVR (p = 0.63) and 1.6 % vs. 2.6 % for vessel thrombosis (p = 0.59). Conclusion: DCB-only strategy is effective in treating LvCAD with comparable outcomes to SvCAD.